Upaya Meningkatkan Motivasi Belajar Melalui Layaan Penguasaan Konten dengan Dukungan Tampilan Kepustakaan Berbasis TIK Di Sma Negeri 2 Ungaran - Hariyadi, Sigit (Indonesian Journal of Guidance and Counseling: Theory and Application, 2012)
Motivation to learn is the overall driving for students to perform a series of learning activities. However, a student in class XIIIPA 2 SMAN 2 Ungaran IPA 2 shows that there are many students who have low motivation in learning. The purpose of this research was to determine whether students motivation can be enhanced through mastery of content services suported by biblio with base of ICT. This type of research is a quasi-experimental design with one group pre-test and post-test. Technique of Sample use total sampling from all population in class XII IPA2 SMA N 2 Ungaran as research subject. Method data collecting use scale motivate to learn. Technique analyses used data namely descriptive analysis of Test and percentage of t (t-test). Students motivation before delivery of services showed an average of 55.58% (medium) and after the delivery of services increased to 66.11% (quite high), this means an increase of 10.53%. The results of the t-test showed that the calculated t-value=11.51 with=1.994, it can be accepted hypothesis. Research shows mastery of content with biblio services are able to foster students self-reliance aspect very well, while the base of ICT in the service is able to provide novelty and appeal to students is an important element of motivation in learning.